2020
DOI: 10.1073/pnas.1917891117
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal cold atmospheric plasma-mediated immune checkpoint blockade therapy

Abstract: Despite the promise of immune checkpoint blockade (ICB) therapy against cancer, challenges associated with low objective response rates and severe systemic side effects still remain and limit its clinical applications. Here, we described a cold atmospheric plasma (CAP)-mediated ICB therapy integrated with microneedles (MN) for the transdermal delivery of ICB. We found that a hollow-structured MN (hMN) patch facilitates the transportation of CAP through the skin, causing tumor cell death. The release of tumor-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
131
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 35 publications
(30 reference statements)
1
131
0
Order By: Relevance
“…Numerous research groups are attempting to investigate and utilize these selective mechanisms of action for biomedical applications. Exemplary mention should be made here of the work of Xu et al [9] on the influence of plasma-generated radicals on the structural modification of gap junctions and the research of Chen et al [10] on CAP-mediated immune checkpoint blockade therapy in a transdermal approach.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research groups are attempting to investigate and utilize these selective mechanisms of action for biomedical applications. Exemplary mention should be made here of the work of Xu et al [9] on the influence of plasma-generated radicals on the structural modification of gap junctions and the research of Chen et al [10] on CAP-mediated immune checkpoint blockade therapy in a transdermal approach.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-programmed death-ligand 1 antibody (aPDL1), an immune checkpoint inhibitor, released from the MN patch further augmented antitumour immunity. Their findings indicate that the proposed transdermal combined CAP and ICB therapy can inhibit the tumour growth of both primary tumours and distant tumours, prolonging the survival of tumour-bearing mice [89].…”
Section: Immunotherapy and Capmentioning
confidence: 95%
“…Recently studied plasma-related immunogenic effects include the use of CAP-mediated immune checkpoint blockade (ICB) therapy integrated with microneedles (MN), described for the transdermal delivery of ICB by Chen et al (2020) [89]. They found that a hollow-structured MN (hMN) patch facilitated the transportation of CAP through the skin, causing tumour cell death.…”
Section: Immunotherapy and Capmentioning
confidence: 99%
See 1 more Smart Citation
“…17 CAP treatment promotes dendritic cell (DC) maturation in the lymph node, where DCs can present the major histocompatibility complexpeptide to T cells. 18 The subsequent T cell-mediated immune response can be augmented by the immune checkpoint inhibitors, resulting in enhanced local and systemic antiviral immunity. The adoptive therapy of CAP should be an ideal choice to be employed or combined with other immune modulating agents for COVID-19.…”
mentioning
confidence: 99%